Influence of cold-water immersion on limb blood flow after resistance exercise - Mawhinney, C.; Jones, H.; Low, D. A.; Green, D. J.; Howatson, G.; Gregson, W. (European Journal of Sport Science, 2017)
This study determined the influence of cold (8°C) and cool (22°C) water immersion on lower limb and cutaneous blood flow following resistance exercise. Twelve males completed 4 sets of 10-repetition maximum squat exercise and were then immersed, semi-reclined, into 8°C or 22°C water for 10-min, or rested in a seated position (control) in a randomized order on different days. Rectal and thigh skin temperature, muscle temperature, thigh and calf skin blood flow and superficial femoral artery blood flow were measured before and after immersion. Indices of vascular conductance were calculated (flux and blood flow/mean arterial pressure). The colder water reduced thigh skin temperature and deep muscle temperature to the greatest extent (P?<?.001). Reductions in rectal temperature were similar (0.2-0.4°C) in all three trials (P?=?.69). Femoral artery conductance was similar after immersion in both cooling conditions, with both conditions significantly lower (55%) than the control post-immersion (P?<?.01). Similarly, there was greater thigh and calf cutaneous vasoconstriction (40-50%) after immersion in both cooling conditions, relative to the control (P?<?.01), with no difference between cooling conditions. These findings suggest that cold and cool water similarly reduce femoral artery and cutaneous blood flow responses but not muscle temperature following resistance exercise.